Islamic Education Practices Through Parenting Styles in the Palembang Malay Tribe - Sukirman, Sukirman; Khodijah, Nyayu; Baiti, Masnun; Ramdani, Zulmi (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
The aim of this research is to describe the Islamic education through parenting style in the Muslim family tradition of the Palembang Malay tribe. The research was conducted in the Palembang city. The citizens of the city of Palembang are known for their pious and devouted residents in fulfilling religious obligations. This can be seen by the bustling of Muslim citizens visiting the Grand Mosque for Friday prayers, during the holy month of Ramadan, and the relatively high interest of the Palembang Malay citizens to perform Haj since the 1980s. This study used a qualitative approach with a case study design. The sampling technique used is non-probability sampling with purposive sampling. Respondents in this study were some families whose parents’ jobs differ with each other. Meanwhile, the children varied from toddlers, teenagers to adults. Data was collected from in-depth interviews and observations while data analysis used interactive analysis which included 4 stages: data reduction, data presentation, data interpretation, and drawing conclusions. The results of this study show that: (1) Islamic education implemented through parenting styles in Palembang Malay Muslim families is generally democratic, although there are still some authoritarian elements; and (2) the Islamic values ​​embedded in traditional parenting styles in Palembang Malay Muslim families can be viewed from two perspectives: method and content. From a method perspective, the parenting styles implemented include role models, habituation, and the administration of punishments and rewards. Meanwhile, from a content perspective, the internalized Islamic values ​​include faith education, moral education, and social education. In faith education, parents focus on ensuring children are able to practice religious teachings, possess adequate religious knowledge, and demonstrate good religious attitudes. In moral education, children are guided to understand and apply commendable behavior (akhlaqul karimah) in their daily lives. Meanwhile, in social education, parents strive to instill empathy and a spirit of mutual assistance so that children are sensitive to their social environment.